Development of electronic document management system in tax authorities - T. V. Bratarchuk (State University of Management, 2021)
Currently, an electronic document management system has been widely implemented in the practice of tax authorities, which allows you to reduce time and labor costs for processing and preparing documents; to provide operational services to the population; to ensure the availability and openness of information to the public about the activities of tax authorities, as well as services provided by tax authorities; to reduce the cost of interaction between the population and tax authorities. However, despite the automation of office work, a number of unresolved problems remains in the field of document management of tax authorities.The relevance of this study is that the main problems of the tax authorities are a large number of routine manual operations performed by employees, as well as a large volume of incoming documents that are received by the tax authorities. The creation of documents, as well as their storage, transmission and search for such documents require significant labor, time and financial costs. That is why recently tax inspections have been working on a comprehensive automation of the inspection’s activities by introducing a system for processing and accounting documents, which will allow you after a while to abandon documents and information presented on paper.The study analyses the electronic document management systems used in the practice of public administration, describes the advantages and disadvantages of each system. The paper also analyses the features of the document management process in the tax authorities. Based on the conducted research, the authors propose the introduction of a modern domestic system built on the “Logic of SED”-platform. This system is aimed at improving the efficiency of work in various areas of joint activity of employees of the organization in terms of automation of project document flow and the possibility of collective work.